1990
DOI: 10.1073/pnas.87.9.3363
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IgE synthesis by anti-IgE: role in long-term inhibition of IgE synthesis by neonatally administered soluble IgE.

Abstract: Inoculation of syngeneic IgE into 2-to 12-day-old mice results in prolonged synthesis of anti-IgE antibodies without further challenge. These anti-IgE antibodies may be largely responsible for the long-term inhibition of synthesis of IgE that is known to result from a perinatal challenge with IgE. This conclusion is supported by the effect of passive inoculation of syngeneic polyclonal anti-IgE antibodies into young mice, which similarly results in selective inhibition of IgE synthesis. Further evidence is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…However, few studies have examined the potential to deplete isotype-switched or memory B cells through BCR crosslinking. Two groups have found that perinatal immunization of mice with IgE, prior to the endogenous production of IgE, results in an IgE-specific antibody response that subsequently inhibits the generation of serum IgE in adult mice (29,30). However, immunization of adult mice is not effective due to the development of tolerance against IgE.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined the potential to deplete isotype-switched or memory B cells through BCR crosslinking. Two groups have found that perinatal immunization of mice with IgE, prior to the endogenous production of IgE, results in an IgE-specific antibody response that subsequently inhibits the generation of serum IgE in adult mice (29,30). However, immunization of adult mice is not effective due to the development of tolerance against IgE.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that this is accompanied by profound decreases in the level of serum IgE and the number of IgEsecreting cells in the spleen (4,5 When IgE is inoculated in saline on the day of birth, it fails to elicit anti-IgE antibodies and renders mice tolerant to IgE inoculated on day 9 or 10 (that would otherwise have caused the synthesis of anti-IgE) (4). Tolerance to a challenge on day 9 can similarly be induced by inoculations of small (0.25 ,g) doses of IgE on days 3, 5, and 7; larger amounts of IgE (_5 ,ug) are immunogenic rather than tolerogenic when inoculated on these days (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…KLH evidently provides the necessary T-cell help because adult mice do not respond to unconjugated IgE. Between the ages of 2 and 10 days, however, mice produce anti-IgE antibodies in response to unconjugated IgE administered in complete Freund's adjuvant (4) or in saline (5). The loss of responsiveness to unconjugated IgE correlates with the initial appearance of detectable IgE in serum at the approximate age of 2 wk (4, 5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, anti-IgE antibodies that are useful for treatments, must not be anaphylactogenic and must be capable of neutralizing IgE in the sense that binding of IgE to effector cells of allergy is prevented. In vitro the inhibition of IgE synthesis has also been well documented [5, 6]. …”
Section: Introductionmentioning
confidence: 99%